The value of concomitant testing of cutaneous silent period with sympathetic skin response and heart rate variability in Type-2 diabetes patients: An electrophysiological study - Aya Falah Alrekabi; Safaa Hussein. Alshemmari (Journal of the Pakistan Medical Association)
Objective: To explore the association among cutaneous silent period, sympathetic skin response and heart rate variability in diabetes patients.